Nakai, Mitsuyo (audio interview #1 of 5) - Nakai, Mitsuyo; Hanawa, Yukiko, interviewer
INTERVIEW DESCRIPTION - The first of five interviews with Mitsuyo Nakai was conducted at Lake Elsinore, where she was still running her physical therapy practice.